Challenges in implementing sound solid waste management practices in the informal sector of Gweru, Zimbabwe - Jerie, Steven (Midlands State University, 2015)
This study examines the challenges faced by the waste authorities and informal sector enterprises of Gweru in implementing sound practises in managing solid waste. Dangerous substances such as sulphuric acid from batteries, used oil and chloride are dumped hapharzadly by home industry owners. The sample for questionnaire surveys comprised all the 601 organised informal sector enterprises in Monomotapa high density suburb, Shamrock Park high density suburb, Mkoba high density Suburb, Ascot high Density Suburb, Kudzanai market and Kombayi market. Focus group discussions and interviews with key informants were arranged for the purposes of assessing solid waste management needs and priorities in the informal sector of Gweru and how to improve the waste management system. The main challenges in implementing environmentally sound waste management strategies included operational and logistical constraints such as inadequate vehicles and equipment resulting in erratic collection of waste, obsolete and unsuitable equipment, unqualified personnel, poorly paid and untrained workers. These challenges were attributed to the limited funding for waste management by the waste authorities in the City Council. The institutional and legislative constraints included lack of enforcement of environmental legislation, lack of environmental education, uncontrolled waste dumping and negative public attitudes on waste management and waste work itself. Among the suggested strategies for managing waste, the study recommends that of shared responsibility in waste management among the city council, the enterprise operators and the Environmental Management Agency.